Лексичні засоби вираження експресивності в англомовній новелі - Сухова, Анна Вікторівна (Запорізький національний університет, 2016)
The article deals with the realisation of expressive means on the lexical level of the text. Special attention is paid to the study of such lexical expressive means as epithets, similes, metaphors and their various types. The paper represents the results of the analysis of the above-mentioned stylistic means on the material of Anglophone short stories. The research has shown that Anglophone short stories are characterized by the prevalence of neutral lexical units, however it does not mean that this type of text lacks expressiveness. The most widespread lexical expressive means in Anglophone short stories are epithets, similes and metaphors. Epithets are used to give a detailed description and evaluation of some characters, objects or phenomena and to make a profound impact on a reader. Similes are expressions that create vivid, impressive images, actualise mental activity and develop imagination of a recipient. Metaphors are represented to underline individuality of a certain object, subject or phenomenon and make fictional texts valuable. All these lexical means contribute to expressiveness of the whole Anglophone short story and its separate components and have the pragmatic potential, with the help of which an addressee is influenced in a particular way. Therefore, we can conclude that these lexical expressive means fulfil a pragmatic function, expressing the author’s intentions and attitude to certain characters, phenomena etc. and evoking the reader’s feelings and emotions.
Lexical Expressive Means in an Anglophone Short Story
Keywords: англомовна новела; експресивність; епітет; порівняння; метафора; Anglophone short story; expressiveness; epithet; simile; metaphor